(untitled) (Journal of the College of Basic Education, 2022)
This research is based on the study of ((linguistic analogy)) in the department of the Arabic Language Academy in Cairo, which is one of the methods of language growth, and it is its foundation and general law.As the Academy’s attention to the origins of the language began since its foundation and to the present day, it issued many decisions in it and wrote a book bearing the name ((On the origins of the language)), which is a collection of scientific decisions in four parts, in which it mentioned the analogies in grammar and morphology and in the language and its conditions.This research dealt at its beginning with the meaning of analogy linguistically and idiomatically, and its pillars. and its divisions; And the measurement at the Cairo complex,